The effect of prolonged G-quadruplex stabilization on the functions of human cells - Nargis Karatayeva; Lili Hegedus; Arindam Bhattacharjee; Eszter Nemeth; Adam Poti; Lorinc Pongor; Gabor Juhasz; David Szuts; Peter Burkovics (Scientific Reports)
Abstract Guanine-rich DNA sequences have a propensity to form G-quadruplex structures. These structures play several important biological roles and are potential targets for anticancer drugs. However, no G-quadruplex-stabilizing agent has yet been approved for clinical use. Given that G-quadruplex stabilization is quite promising as a mechanism for novel anticancer therapies, it is crucial to elucidate its effects on healthy human cells. In our study, we modeled a potential human treatment using G4 -stabilizing agents and analyzed their effects on genome integrity, transcriptomic changes, and mitochondrial function focusing on non-cancerous cells to predict potential side effects of such treatments. We found that G-quadruplex stabilization does not compromise genome integrity. However, it can induce persistent alterations in the transcriptomic profile of human cells, including genes encoded on the mitochondrial genome. Notably, certain G-quadruplex-stabilizing agents triggered mitophagy in both human cells and Drosophila melanogaster. In summary, our findings indicate that while G-quadruplex stabilization does not cause genome instability, it may pose potential risks due to its long-term effects on transcription and its ability to induce mitophagy. Therefore, we recommend that all potential drug candidates be thoroughly evaluated for their ability to induce mitophagy and to promote cancer formation in animal models prior to clinical trials.